GD Express Carrier Berhad a drive for excellence : how a culture of "continuous improvement" transforms GDEX from failure to Malaysia's Leading express carrier - Soon, Philemon H.M (Sun Edition Communications, 2013)
A remarkable Malaysian success story -- Teong Teck Lean's unwavering ambition to be a successful entrepreneur led him to revive a near bankrupt company into Malaysia's biggest and most successful express courier services company.